"Let's Get Together and …": Starting and Continuing Allen Creek, a Psychoanalytic School. Issue 1 (1st January 2018) - Novick, Kerry Kelly; Novick, Jack
ABSTRACT: In this paper, the authors describe the long tradition of psychoanalysts and educators working together for the benefit of children and families. They recount the inception and evolution of one nonprofit psychoanalytic school, Allen Creek Preschool in Ann Arbor, Michigan, in terms of the conceptual and practical underpinnings their group brought together. Stories of work by psychoanalyst "family consultants, " teachers, parents, and children illustrate the partnerships formed and the impact on all concerned in building emotional muscle and mastering developmental transitions and transformations.